2023
DOI: 10.1111/jocd.15832
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Novel leg vein treatment CLaCS guided by augmented reality 11 years follow‐up

Kasuo Miyake,
Marcelo Halfen Grill,
Heidi Shiho Nagatani Feitoza

Abstract: Telangiectasias is most prevalent on the lower limbs and has been estimated to manifest in 40%–90% of the population. Treatments for telangiectasias include sclerotherapy, laser therapy, intense pulsed light treatment, microphlebectomy, and thermocoagulation. Cryo‐Laser & Cryo‐Sclerotherapy (CLaCS) effectively combines thermal and injection sclerotherapy. In this treatment, unwanted veins are targeted by a transdermal laser and immediately receive injection sclerotherapy. During the whole procedure, an air‐coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Previous studies have demonstrated the success of combining transdermal laser treatment with the use of sclerosants in the treatment of lower extremity varicose veins. 5 , 6 , 7 , 8 Dinache et al 10 (2020) demonstrated that the laser can interact with the foam, further reducing its microbubbles and increasing its stability, as well as allowing better interface interaction with the tissue. Additionally, external cooling provided by cold air prevented damage to the skin surface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated the success of combining transdermal laser treatment with the use of sclerosants in the treatment of lower extremity varicose veins. 5 , 6 , 7 , 8 Dinache et al 10 (2020) demonstrated that the laser can interact with the foam, further reducing its microbubbles and increasing its stability, as well as allowing better interface interaction with the tissue. Additionally, external cooling provided by cold air prevented damage to the skin surface.…”
Section: Discussionmentioning
confidence: 99%
“…This technique is based on that used by Moreno-Moraga et al; however, we only use the 6-mm spot size to treat all venous calibers as proposed by Miyake et al. 5 Furthermore, we use higher and more constant energy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation